Global biogeography of marine amphipod crustaceans: latitude, regionalization, and beta diversity - Arfianti, Tri; Costello, Mark J (Marine Ecology Progress Series, 2020)
Studying the biogeography of amphipod crustaceans is of interest because they play an important role at lower trophic levels in ecosystems. Because they lack a planktonic larval stage, it has been hypothesized that marine benthic amphipod crustaceans may have short dispersal distances, high endemicity, and spatial turnover in species composition, and consequently high global species richness. In this study, we examined over 400000 distribution records of 4876 amphipod species, and identified 12 regions of endemicity. The number and percent of endemic species peaked at 30°-35°S and coincided with 3 of these regions of high endemicity: Australia, New Zealand, and southern Africa. Pelagic species of marine amphipod crustaceans were more cosmopolitan than benthic species. The latitudinal patterns of richness (alpha, gamma, and ES50) and species turnover were at least bimodal. Most occurrence records and greater alpha and gamma richness were in mid-latitudes, reflecting sampling bias. Both ES50 and beta diversity had similar richness in the tropics, mid-latitudes, and on the Antarctic shelf around 70°S. These 2 indices exhibited a sharp dip in the deep Southern Ocean at 55°S. ES50 peaked at 30°-35°S and a small dip was apparent near the equator at 5°-10°N. Beta diversity was driven mostly by turnover rather than nestedness. These findings support the need for conservation in each realm of species endemicity and for amphipods, particularly in Antarctica and the coastal mid-latitudes (30°-35°S) of the Southern Hemisphere. KEYWORDS: Endemicity · Latitudinal gradients · Conservation · Species richness · Species turnover
Keywords: Sørishavet; biogeografi; crustacea; krepsdyr; marin biologi; marine økosystemer; zoogeografi

A survey of amphipod associates of sea urchins, with description of new species in the genera Lepidepecreella (Lysianassoidea: lepidepecreellid group) and Notopoma (Photoidea: Ischyroceridae) from Antarctic cidarids - Berge, Jørgen; Vader, Wim; Lockhart, Susanne (ANDEEP (Antarctic benthic DEEP-sea) biodiversity: colonization history and recent community patterns: a tribute to Howard L. Sanders, 2004)
The known associations between amphipods and echinoids are listed, separated into five different categories depending upon the nature of the associations. The new species Lepidepecreella andeep, found attached around the mouth of the cidarid sea urchin Aporocidaris antarctica, is described, as well as the new species Notopoma cidaridis. The tubes of the latter were found attached to the spines of the cidarid sea urchin Rhynchocidaris triplopora. These cases represent the first associations reported between amphipods and echinoids in the Antarctic. A key to both genera is provided.
Keywords: Sørishavet; Weddellhavet; amfipoder; krepsdyr; pigghuder; sjøpiggsvin; taksonomi; zoologi

Cold resistance and metabolic responses to salinity variations in the amphipod Eusirus antarcticus and the krill Euphausia superba - Aarset, Arne V.; Torres, Joseph J. (Polar Biology, 1989)
The krill Euphausia superba, unlike the amphipod, Eusirus antarcticus, tolerates being frozen into solid sea-ice at temperatures down to about-4°C. Cooled in air, the amphipod and the krill freeze and will die at temperatures of-11° and-9°C respectively, representing the supercooling points of the animals. The krill is an osmoconformer in the salinity range of 25 to 45 ppt, while the amphipod conforms in the salinity range of 26 to 40 ppt. The animals thereby lower the melting point of their body fluids in the vicinity of the freezing sea ice, preventing internal ice formation at low temperatures. The mean oxygen consumption rates, at raised and lowered salinities, were not significantly different from rates obtained in normal (35 ppt.) seawater, indicating that salinity has little effect on the metabolism of either species.
Keywords: Sørishavet; krepsdyr; krill; kuldetoleranse; marin biologi; plankton

Size Frequency Pattern of Euphausia Superba in the Antarctic Peninsula Waters in the Austral Summer of 1983 - Fevolden, Svein Erik; George, Robert Y. (Journal of Crustacean Biology, 1984)
In the austral summer of 1983, schools of krill from Bransfield Strait and Palmer Archipelago were analyzed for composition in terms of size frequencies and maturity stages. Juveniles dominated in all schools, and mature animals never exceeded 6.8% of the animals at any sampling site. Gravid females were encountered in only four out of 15 schools and were never more frequent than 1.8% of the animals in any school. Among subadults and juveniles the largest animals were found on the inside of Palmer Archipelago. Smaller nonreproductive animals were on the outside and in Bransfield Strait. A second group of juveniles, in a size range of 12-15 mm, was more pronounced north of Crocker Passage than south of the Passage. Their potential origin from a more slowly growing and later spawning Southern Weddell Sea population is discussed. Lack of reproductive animals in the Bransfield/South Shetlands vicinity may reflect yearly variation in this region. A hypothesis is put forward on the basis of this study that Palmer Archipelago is a nursery ground for krill spawned elsewhere. The sites of origin of this krill could be ascertained on the basis of studies of enzyme polymorphism in these populations.
Keywords: Sørishavet; Weddellhavet; krepsdyr; krill; marin biologi; plankton

The swarming of krill and problems of estimating the standing stock - Mackintosh, N A (Norsk hvalfangst-tidende, 1966)
Keywords: Sørishavet; krepsdyr; krill; marinbiologi

Antarctisk hval-aate - Broch, Hjalmar (Norsk hvalfangst-tidende, 1930)
Keywords: Sørishavet; krepsdyr; krill; litteratur; marin biologi